2020
DOI: 10.1115/1.4045933
|View full text |Cite
|
Sign up to set email alerts
|

Internet-of-Things-Enabled Dual-Channel Iontophoretic Drug Delivery System for Elderly Patient Medication Management

Abstract: Wireless controllers have found its application in the supervision of the patients in the hospitals. It is not only a valid issue for the developing countries but also for the developed countries. For this reason, scientists are working on the advancement of medical devices that are capable of decreasing the workload of health caregivers. In this study, the development of an iontophoretic drug delivery device that could be controlled using a mobile is described. For the purpose, hardware and a software module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Wireless controllers are now essential in healthcare, with researchers exploring advanced medical devices for efficient medication delivery. In research work [56], a smartphone-controlled iontophoretic drug delivery device with a hardware module and mobile app for drug delivery control was developed. It features a safety mechanism to detect loose leads and stop drug delivery.…”
Section: Research Survey For Exploring the Role Of Iot In Revolutioni...mentioning
confidence: 99%
“…Wireless controllers are now essential in healthcare, with researchers exploring advanced medical devices for efficient medication delivery. In research work [56], a smartphone-controlled iontophoretic drug delivery device with a hardware module and mobile app for drug delivery control was developed. It features a safety mechanism to detect loose leads and stop drug delivery.…”
Section: Research Survey For Exploring the Role Of Iot In Revolutioni...mentioning
confidence: 99%
“…Control over medication and equipment: Although not restricting the scope within a healthcare infrastructure, the IoT empowers the management and control over medication [ 62 ] and medical sensory equipment [ 63 ]. Continuous as well as real-time monitoring [ 64 ] and control of production units [ 65 ] can help such automated industries keep up with the challenges faced while meeting end users’ expectations.…”
Section: Fundamentals Of Internet Of Things-enabled Healthcare Systemsmentioning
confidence: 99%
“… 284 As a comprehensive system for mobile-controlled drug delivery, Reddy et al reported a dual-channel iontophoresis device with a contact failure-detecting module. 285 …”
Section: Skin Devices Based On the Electrical Features Of The Skinmentioning
confidence: 99%